2013
DOI: 10.1111/bjd.12060
|View full text |Cite
|
Sign up to set email alerts
|

A 24-week randomized clinical trial investigating the efficacy and safety of two doses of etanercept in nail psoriasis

Abstract: Both ETN regimens were effective at treating nail psoriasis in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
3
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 35 publications
(135 reference statements)
7
41
3
3
Order By: Relevance
“…In the same study,patients treated with cyclosporine showed a 37% mean improvement in the NAPSI score (21 (25). The efficacy of etanercept in nail psoriasis has also been supported by other studies (7,26,27). In our case, there was a rapid response to etanercept with a significant reduction in the NAPSI score.…”
Section: Case Reportsupporting
confidence: 83%
“…In the same study,patients treated with cyclosporine showed a 37% mean improvement in the NAPSI score (21 (25). The efficacy of etanercept in nail psoriasis has also been supported by other studies (7,26,27). In our case, there was a rapid response to etanercept with a significant reduction in the NAPSI score.…”
Section: Case Reportsupporting
confidence: 83%
“…Eine retrospektive Analyse der EXPRESS Studie zeigte, dass bei einjähriger Nachbeobachtung von 186 Patienten mit anfänglich positivem Ansprechen auf Infliximab nachhaltig verbesserte PASI-, DLQIund NAPSI-Werte auch noch nach der 50. Ortonne et al untersuchten Wirksamkeit, Sicherheit und Verbesserungen mit zwei Etanercept-Dosierungen bei Patienten mit mittelschwerer bis schwerer Psoriasis und Nagelbeteiligung [15]. Damit wurde nachgewiesen, dass Infliximab Nagelveränderungen und die Lebensqualität verbessert und als äußerst geeignet für die Behandlung von NP anzusehen ist [2].…”
Section: Patienten Und Methodenunclassified
“…There was a significant improvement in mean NAPSI scores at week 24 in both groups, with significant number of patients showing complete resolution. Both treatment regiments were found to be effective in nail psoriasis [60]. In the post hoc analysis of a RCT, in which the patients were randomized to receive either continuous (25 mg twice weekly for 54 weeks) or paused (50 mg twice weekly up to 12 weeks, followed by 25 mg twice weekly in case of relapse) etanercept therapy, 564 patients with nail involvement were evaluated.…”
Section: Biologic Treatmentsmentioning
confidence: 99%